Martin Luther's Philosophy of Thought on Indulgences and Lessons Learned in Today's Ministry - Lumoindong, Gilbert E; Pakpahan, Gernaida KR (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Various criticisms made by Martin Luther occurred when he learned of the practice of selling confessions by church authorities in that era. Moreover, the initial attack carried out by Martin Luther to spearhead the church reform movement in Germany was by installing 95 theses on the door of the church in Wittenberg. That is why this paper will describe Luther's main idea about indulgences which is revealed in some of his arguments (read: theses) that made many people disturbed and threatened, so the church authorities designed a scenario to minimize Martin Luther's attack. This journal uses a descriptive-historical qualitative approach; it is said that the author examines it by tracing the sources contained in the literature regarding the characters studied and linking them to the church today. Of course, there will be limitations in the study. The author hopes there will be further research on this church figure, especially in other studies.